Analisis Motif Pekerja Migran Perempuan Lampung Timur Bekerja di Luar Negeri - Simbolon, Khairunnisa; Sanjaya, Fitri Juliana; Fadhillah, Nibras (Wacana Publik, 2024)
The informal sector is still an option for Lampung people who want to work abroad. The majority of workers from Lampung work as domestic workers and caregivers, it is not surprising why women dominate PMI Lampung. People definitely have various reasons why they choose to work abroad. However, minimal studies on this matter have been carried out, and instead there is more research on the protection of PMI and various problems faced abroad. This research wants to fill the gap in the discussion of PMI motives, especially those from East Lampung Regency. East Lampung was chosen because it is the district with the most PMI exporters in Lampung Province. The fact that women dominate PMI from Lampung is also a factor that needs to be studied, because it will really help related parties in formulating policies related to female PMI. The results of this research show that East Lampung female migrant workers' motives for choosing to work abroad consist of push factors (lack of job opportunities and low wages), pull factors (high salaries and shared language), labor shortages in their country of origin, as well as economic factors, namely to help the family economy.